2019
DOI: 10.5213/inj.1938062.031
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Obesity and the Nocturia in the U.S. Population

Abstract: Purpose We aimed to investigate the association of obesity with nocturia using a nationally representative sample of adults from the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2012. Methods A total of 14,135 participants were included in this study. We performed a multivariate logistic regression analysis to find the odds ratio (OR) of obesity for nocturia. Furthermore, the OR of BMI for nocturia was analyzed using restricted cubic spline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…In this study, the risk of hypertension incidence increased nonlinearly with continuous change of BMI or WHtR. Similar results were reported that signi cant nonlinear association between the continuous change of BMI and hypertension after adjusting the covariates strati ed by gender and age groups indicating a dose-response relationship between adiposity indices and hypertension (39). Moreover, the other studies support our results hold that weight loss could lower blood pressure in both hypertension and non-hypertension population (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the risk of hypertension incidence increased nonlinearly with continuous change of BMI or WHtR. Similar results were reported that signi cant nonlinear association between the continuous change of BMI and hypertension after adjusting the covariates strati ed by gender and age groups indicating a dose-response relationship between adiposity indices and hypertension (39). Moreover, the other studies support our results hold that weight loss could lower blood pressure in both hypertension and non-hypertension population (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…Fitzgerald et al 2 found that the odds ratio of nocturia increased with age and BMI in a multivariate model. Other studies also reported that nocturia was signi cantly associated with obesity 11,12 . Similarly, in the present study, age older than 30 years, BMI over 25 kg/m 2 , and presence of moderate to severe LUTS were predictive factors for nocturia in our sample of young Asian men.…”
Section: Discussionmentioning
confidence: 92%
“…Debates are still ongoing as to whether decreased BMI leads to decreased nocturia or not, although there has been a report that reveals that decreased BMI does indeed lead to decreased nocturia [ 33 ]. Contrarily, other studies have revealed that a higher BMI is related to decreased nocturia [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%